2017
DOI: 10.1007/s00784-017-2284-y
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial manifestations in outpatients with anorexia nervosa and bulimia nervosa focusing on the vomiting behavior

Abstract: ED outpatients were found to present a higher incidence of oral-related complications and an inferior oral health status, compared to gender- and age-matched controls. Alterations verified within outpatients were acknowledged to be quite similar to those previously reported within inpatients, in both of nature and severity, thus sustaining that the cranio-maxillofacial region is significantly affected by ED, even in the early/milder forms of the condition, as expectedly verified within outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 48 publications
3
62
1
7
Order By: Relevance
“…The present study did not find differences in periodontal health between the groups. This finding agrees with Lourenço et al (24), who concluded that variations in results could be due to the differences in oral hygiene maintenance within the study population. Johansson et al (12) obtained a lower incidence of gingival bleeding in ED patients than a control group; the authors believed that this could be due to the fact that patients with EDs consider oral hygiene more important than control group subjects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study did not find differences in periodontal health between the groups. This finding agrees with Lourenço et al (24), who concluded that variations in results could be due to the differences in oral hygiene maintenance within the study population. Johansson et al (12) obtained a lower incidence of gingival bleeding in ED patients than a control group; the authors believed that this could be due to the fact that patients with EDs consider oral hygiene more important than control group subjects.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of saliva flow in patients with EDs has been measured in numerous research papers (12,24,5). Our results show a significant decrease in the group of the EDG.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin deficiency can aggravate periodontal disease and contribute to the rapid development of gingival inflammation and periodontal pockets . Vitamin C deficiency may result in reduced collagen synthesis, increased permeability of the crevicular epithelium to bacterial products, decreased integrity of the periodontal microvasculature, increased permeability to bacterial products, and reduced host immune response, delaying the motility of polymorphonuclear leukocytes . We observed that the ABN group presented worse periodontal health than the CN group.…”
Section: Discussionmentioning
confidence: 67%
“…Authors report that bulimia is a variant of anorexia nervosa, concluding that bulimia may be an earlier form of this disease [27]. There are oral alterations that may increase the suspicion of a patient with bulimia, including larger jugal regions, signs of trauma in the jugal region, perimylolysis, dental erosion, dental hypersensitivity and increased visible vascularization of the entire oral mucosa; all these signs can be observed in patients with recurrent vomiting [10,28,29].…”
Section: Discussionmentioning
confidence: 99%